Analisis Pengaruh Kepribadian Individu dan Keberagaman di Tempat Kerja Terhadap Kinerja Karyawan pada Percetakan Digital Printing Zaky - Aksa Zaid; Agtary Zacky; Vivi Nila Sari (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
This research aims to identify the types of personality that tend to contribute positively to performance in printing, Understand how diversity in terms of background, education and experience can influence team collaboration and output quality in printing, Investigate whether there are certain factors related to personality or diversity that can hinder performance, Ensure that this analysis also considers the impact on the employee's overall quality of work life. By understanding how personality and diversity impact performance, companies can promote a more inclusive and supportive work environment for all team members